Groundwater elevation estimation model in the sloping Ogallala aquifer - Mzava, Philip G. (Kansas State University, 2010)
A one-dimensional model was developed to study the flow of groundwater in the sloping Ogallala Aquifer at a steady state during predevelopment condition. The sloping base was approximated using a stepping base model. GIS applications were applied during data collection and preparation, and later during interpretation of model results. Analytical and numerical methods were employed in the development of this model which was used to try to understand long-term water balance in the study region. The conservation of mass was achieved by balancing groundwater input, output, and storage; this led to understanding the interactions of groundwater and surface water in the predevelopment conditions. The study resulted in identification of where natural discharge from groundwater to surface water occurred, and the quantity of these flows was obtained. The Ogallala Aquifer is thick in the south western part of Kansas, this region had an average saturated thickness of 100m during predevelopment conditions. The model found that groundwater flowed at a discharge per width of approximately 17 m[superscript]2/d in this region. The aquifer thickness tends to gradually decrease from west to east and from south to north. The northern part had an average saturated thickness of 40m during predevelopment conditions; the model found that groundwater flowed at a discharge per width of approximately 3 m[superscript]2/d in this region. It was also found that groundwater leaves the Ogallala Aquifer on the eastern side with discharge per width between 0-3 m[superscript]2/d. The discharge from groundwater to surface water was summed over contributing areas to river basins. The discharge to streams necessary to satisfy long-term conservation of mass computed by the model showed that Cimarron River has total baseflow of about 5.5 m[superscript]3/s; this was found to be almost 100% of the total streamflow recorded during predevelopment conditions. The Arkansas River was found to have total baseflow of about 0.97 m[superscript]3/s, which is approximately 14.3% of the total streamflow recorded during predevelopment conditions. The Smoky Hill River was found to have total baseflow of about 1.7 m[superscript]3/s, which is approximately 73.9% of the total streamflow recorded during predevelopment conditions. The Solomon River was found to have total baseflow of about 0.95 m[superscript]3/s, which is approximately 41.1% of the total streamflow recorded during predevelopment conditions. The Saline River was found to have total baseflow of about 0.25 m[superscript]3/s, which is approximately 62.5% of the total streamflow recorded during predevelopment conditions. The Republican and Pawnee River was found to have total baseflow of about 0.38 m[superscript]3/s and 0.22 m[superscript]3/s, which is approximately 18.5% and 12.6% of the total streamflow in the predevelopment conditions respectively. The model was found to be always within -16 to +12 meters between observed values and the model results, with an average value of 0.15m and a root mean square error of 1.98m. Results from this study can be used to advance this study to the next level by making a transient model that could be used as a predictive tool for groundwater response to water use in the study region.
Keywords: Groundwater; Ogallala Aquifer; Sloping; Model; Engineering, Civil (0543); Hydrology (0388)